EFFECT OF TIME VARIATION ON XYLENE USING ACTIVE CARBON FROM WASTE OF BANANA STEM (Musa paradisiaca L) - Ashari, Ayu Wanti; -, Alimuddin; Sitorus, Saibun (Jurusan Kimia FMIPA UNMUL, 2020)
Test of activated carbon adsorption ability of banana stem waste (Musa paradisiaca L) on xylene has been carried out. In the characterization of activated carbon Scanning Electron Microscopy (SEM) was used to show the morphological differences in activated carbon after activation and before activation while xylene adsorption using a UV spectrophotometer with variations in the time of adsorption. The optimum xylene adsorption time was obtained on the weight of 0.4 gram adsorbent, the concentration of xylene 40 ppm was 45 minutes, the adsorption capacity was 1.772 mg/g.